An interface nucleation rate limited sintering kinetic model applied to in situ sintering Al2O3-SmAlO3 composites. Issue 8 (July 2023) - Dillon, Shen J.; Ma, Yonghui; Lang, Eric; Ouyang, Jia-hu; Hattar, Khalid
Abstract: A nucleation rate limited sintering model was recently developed based on observations of bicrystal sintering. This work validates the applicability of this model for sintering of polycrystalline clusters of Al2 O3 -SmAlO3 at high temperature in the range of 1130–1610 ℃. The model fits the data well and agrees with trends observed during bicrystal sintering. A temperature dependence to the dominant sintering strain deformation modes is observed from in situ heating experiments performed in a transmission electron microscope (TEM). The observations provide insights into how temperature influences the early stages of sintering by affecting the pore size distribution through local de-sintering. This provides insights into the role heating rate and sintering schedule play in microstructural evolution that influences the grain size versus density trajectory.